Assessing the Status Quo of EHR Accessibility, Usability, and Knowledge Dissemination. Issue 1 (25th May 2018) - Khairat, Saif; Coleman, George Cameron; Russomagno, Samantha; Gotz, David
Aim: This study was performed to better characterize accessibility to electronic health records (EHRs) among informatics professionals in various roles, settings, and organizations across the United States and internationally. Background: The EHR landscape has evolved significantly in recent years, though challenges remain in key areas such as usability. While patient access to electronic health information has gained more attention, levels of access among informatics professionals, including those conducting usability research, have not been well described in the literature. Ironically, many informatics professionals whose aim is to improve EHR design have restrictions on EHR access or publication, which interfere with broad dissemination of findings in areas of usability research. Methods: To quantify the limitations on EHR access and publication rights, we conducted a survey of informatics professionals from a broad spectrum of roles including practicing clinicians, researchers, administrators, and members of industry. Results were analyzed and levels of EHR access were stratified by role, organizational affiliation, geographic region, EHR type, and restrictions with regard to publishing results of usability testing, including screenshots. Results: 126 respondents completed the survey, representing all major geographic regions in the United States. 71.5 percent of participants reported some level of EHR access, while 13 percent reported no access whatsoever. Rates of no-access were higher among faculty members and researchers (19 percent). Among faculty members and researchers, 72 percent could access the EHR for usability and/or research purposes, but, of those, fewer than 1 in 3 could freely publish screenshots with results of usability testing and half could not publish such data at all. Across users from all roles, only 21 percent reported the ability to publish screenshots freely without restrictions. Conclusions: This study offers insight into current patterns of EHR accessibility among informatics professionals, highlighting restrictions that limit dissemination of usability research and testing. Further conversations and shared responsibility among the various stakeholders in industry, government, health care organizations, and informatics professionals are vital to continued EHR optimization.